PENGARUH PEMBERIAN SARI KACANG HIJAU TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU NIFAS DI PMB KURNIA KECAMATAN DELI TUA KABUPATEN DELI SERDANG TAHUN 2023 - Sitepu, Marlen Sadrina; insani, septa dwi (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2023)
Breast milk (ASI) is the most optimal source of nutrition for babies during the first six months of growth, without the need for additional liquids or solid foods. Green bean juice is a drink that contains lactagogue and polyphenols. A lactagogue is a food that can increase and facilitate the production of breast milk, while polyphenols can stimulate the release of prolactin, which increases milk production and triggers oxytocin to facilitate milk secretion. The purpose of this study is to evaluate the differences in breast milk production after delivery before and after consumption of green bean juice in PMB Kurnia, Deli Tua District, Deli Serdang Regency in 2023. The research used in this study is quasi-experimental. Using a single-group pretest-posttest design. The study and sample consisted of a total of 10 participants selected through purposive sampling. Data were collected through observation forms and questionnaires from 1 to 8. until June 2023 in Deli Tua district Deli Serdang regency PMB Kurnia. An independent Wilcoxon signed-rank test was used for statistical analysis. The results showed that women who gave birth after consuming green bean juice had an average breast milk production of 2.90 compared to 1.20 before consuming green bean juice. The average difference in breast milk production between the two groups was 1.70 with a p-value of 0.004 (ρ andlt; 0.05). This indicates the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha) which is the effect of green bean juice on increasing production of breast milk in postpartum women after its consumption compared to the period before its consumption in PMB Kurnia. Kurnia, Deli Tua District, Deli Serdang Regency in 2023. From the results of this study, it is hoped that health workers can motivate postpartum women to consume mung beans which can increase breast milk production.